2011
DOI: 10.1007/s11274-011-0677-7
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformations of cinnamaldehyde, cinnamic acid and acetophenone with Mucor

Abstract: A strain JX23 was isolated from soil and identified as a species of Mucor according to the morphological characteristics and the nuclear ribosomal internal transcribed spacer sequence and designated as Mucor sp. JX23. Biotransformations of cinnamaldehyde (CMD), cinnamic acid (CMA) and acetophenone (ACP) catalyzed by JX23 were investigated. After JX23 was cultured for 48 h, the substrates CMD, CMA and ACP were added to the growth medium respectively and the products were analyzed by GC-MS and HPLC. Mucor sp. JX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…To date, only a few studies focused on the analysis of these two compounds have been reported in the scientific literature: for CAD (Blakemore and Thompson 1983; Tsai and Chen 1984;Gursale et al 2010;Ma et al 2011;Zhao et al 2014) and for DAD (Germain et al 2002;Hsieh et al 2012;Casella et al 2013;Zhao et al 2013). Due to their volatility, GC was the preferred instrumental separation technique.…”
Section: Analytical Methods Development and Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only a few studies focused on the analysis of these two compounds have been reported in the scientific literature: for CAD (Blakemore and Thompson 1983; Tsai and Chen 1984;Gursale et al 2010;Ma et al 2011;Zhao et al 2014) and for DAD (Germain et al 2002;Hsieh et al 2012;Casella et al 2013;Zhao et al 2013). Due to their volatility, GC was the preferred instrumental separation technique.…”
Section: Analytical Methods Development and Optimizationmentioning
confidence: 99%
“…After reviewing the methods that analyze CAD or CAD and make use of GC-MS (Ma et al 2011;Casella et al 2013;Zhao et al 2013Zhao et al , 2014, a protocol very similar to the one described in BInstrumental analysis^section was proposed as a starting point in the optimization. Overall, the method worked well.…”
Section: Instrumental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been immobilized in polyvinyl alcohol (PVOH) beads, nylon 6.6 pellets and cellulose triacetate films (Appendini and Hotchkiss, 1997), and in cross-linked PVOH films (PVOH) Conte et al, 2006;Conte et al, 2007); incorporated in mono and multilayer cross-linked PVOH structures (Buonocore et al, 2005), composite films of plasma-treated spelt bran and cross-linked PVOH (Mastromatteo et al, 2011), low density polyethylene (LDPE), polycaprolactone (PCL), and poly(lactic acid) (PLA) (del Nobile et al, 2009), and whey protein coatings (Min et al, 2008); microencapsulated in zein (Jin et al, 2009;Zhong et al, 2009), and encapsulated in supramolecular hydrogels based on α-cyclodextrin and water-soluble PCL-poly(ethylene glycol) block copolymer (Ma et al, 2011).…”
Section: 60) Minimal Inhibitory Concentrations (Mic) Obtained Bymentioning
confidence: 99%
“…However, it is difficult to know the real concentration or amount released that prevents fungal growth, since, although the volatile is released into the head-space, (i) the agar can absorb a part of the volatile, (ii) some leakage may be expected in the Petri dish because it is not a hermetically-sealed system, (iii) a saturation of the head-space could be achieved before releasing all the compound present in the film, (iv) the partition coefficient of cinnamaldehyde between the film and the air influences the final head-space concentration (Kurek et al, 2013), and (v) the fungi can biotransform or metabolize some cinnamaldehyde into other compounds as has been demonstrated by Ma et al (2011).…”
Section: Effectiveness In Vitro Of the Antifungal Gliadin Films Incmentioning
confidence: 99%